Plasma Glycosaminoglycans: A new Promising tool for Assessment of Non-Metastatic Renal Cell Carcinoma Patients Following Nephrectomy - ALi, Awais; Omneya, Abdelkarem; Adil, Kashif (Novelty in Biomedicine, 2024)
Background: Non-invasive detection of renal cell carcinoma (RCC) recurrence is a major challenge that could radically affect patient survival. To date, there are no approved biomarkers for inclusion in the monitoring and follow-up of RCC; therefore, assessment of treatment response is lacking. Materials and Methods: A Cross-sectional study was carried out on biopsy-proven renal cell carcinoma patients scheduled for nephrectomy at Hayatabad Medical Complex (HMC) Hospital, Peshawar, Pakistan, between September 2022 and January 2024. Results: A total of 160 samples were included in the study. Eighty samples were obtained from biopsy-proven non-metastatic renal cell carcinoma patients, of which 40 were collected pre-nephrectomy, 40 were collected post-nephrectomy from the same patients, and 80 samples were collected from age and gender-matched healthy individuals. Total plasma glycosaminoglycans (GAGs) levels were analyzed through a manual enzyme-linked immunosorbent assay using a non-competitive sandwich technique. Quantitative variables were summarized as means and standard deviation, while qualitative variables were summarized as frequency and percentage. A paired t-test was performed to check whether the difference between the mean plasma GAG levels in pre-nephrectomy and post-nephrectomy groups was significant. Conclusion: The results revealed that post-nephrectomy GAG levels have significantly decreased compared to pre-nephrectomy levels (P<0.001). Plasma glycosaminoglycan levels could be promising markers for monitoring renal cell carcinoma patients post-nephrectomy.